MST2 kinase suppresses rDNA transcription in response to DNA damage by phosphorylating nucleolar histone H2B. (22nd May 2018) - Pefani, Dafni Eleftheria; Tognoli, Maria Laura; Pirincci Ercan, Deniz; Gorgoulis, Vassilis; O'Neill, Eric
Abstract: The heavily transcribed rDNA repeats that give rise to the ribosomal RNA are clustered in a unique chromatin structure, the nucleolus. Due to its highly repetitive nature and transcriptional activity, the nucleolus is considered a hotspot of genomic instability. Breaks in rDNA induce a transient transcriptional shut down to conserve energy and promote rDNA repair; however, how nucleolar chromatin is modified and impacts on rDNA repair is unknown. Here, we uncover that phosphorylation of serine 14 on histone H2B marks transcriptionally inactive nucleolar chromatin in response to DNA damage. We identified that the MST2 kinase localises at the nucleoli and targets phosphorylation of H2BS14p in an ATM‐dependent manner. We show that establishment of H2BS14p is necessary for damage‐induced rDNA transcriptional shut down and maintenance of genomic integrity. Ablation of MST2 kinase, or upstream activators, results in defective establishment of nucleolar H2BS14p, perturbed DNA damage repair, sensitisation to rDNA damage and increased cell lethality. We highlight the impact of chromatin regulation in the rDNA damage response and targeting of the nucleolus as an emerging cancer therapeutic approach. Synopsis: Transient transcriptional shutdown upon nucleolar DNA damage helps ensure genome integrity of highly repetitive rDNA. This involves chromatin regulation via histone H2B phosphorylation by ATM‐activated MST2 kinase. MST2 localizes in the nucleolus and interacts with nucleolar chromatin in response to DNA damage. MST2 phosphorylates histone H2B at serine 14 upon ATM activation. MST2 activity results in RNA polymerase I inhibition in response to DNA damage. MST2‐dependent Pol I transcriptional shut‐down promotes cell survival in the presence of rDNA damage. Abstract : Transient transcriptional shutdown via ATM‐dependent chromatin regulation ensures genome integrity upon DNA breaks in the nucleolus.